133k views
3 votes
I know I just fill in -1 with x but I’m stuck with 2 different answers and this is an exam sooooo I don’t wanna risk it. Can someone please tell me the answer?

I know I just fill in -1 with x but I’m stuck with 2 different answers and this is-example-1
User Thmsn
by
5.8k points

1 Answer

2 votes

Answer:

g(-1) = 4

Explanation:

Given:

g(x) =
(3x^2 - 2x + 7)/(2x + 5)

To find g(-1), substitute x = -1

Thus:

g(-1) =
(3(-1)^2 - 2(-1) + 7)/(2(-1) + 5)

g(-1) =
(3 + 2 + 7)/(-2 + 5)

=
(3 + 2 + 7)/(-2 + 5)

=
(12)/(3)

g(-1) = 4

User Anibalajt
by
5.6k points